Evaluasi Tata Kelola Teknologi Informasi Dinas Komunikasi dan Informatika Kota Batu Menggunakan Kerangka Kerja COBIT 4.1 dengan Domain Deliver and Support (DS) dan Monitor and Evaluate (ME) - Dindha Maria Ulfa; Suprapto Suprapto; Yusi Tyroni Mursityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Dinas Komunikasi dan Informatika Kota Batu is a government agency that has the task of carrying out regional authority in the field of ICT management. Based on the results of the interview found several problems such as there is no complete documentation and does not yet have a standardized standard on several IT governance processes and lack of optimal human resource management, so that such problem management and allocation of costs do not have clear process steps. In order for existing IT management to be in accordance with organizational goals, an IT evaluation is needed to find out the solutions to existing problems. In this study discussed the evaluation of IT governance using the COBIT 4.1 framework with the focus of the DS and ME domains. The purpose of this study is to measure the current maturity level values ​​that can determine the current state or position of the organization to then be able to provide recommendations for improvement to achieve the expected maturity level of the organization's position based on the results of analysis conducted from the results of data collection. From the calculation of the assessment sheet filled by respondents based on the RACI Chart, the average value of the DS domain is 1.62 and the ME domain is 1.75. The recommendation given is to make a Standard Operating Procedure (SOP) in every existing IT process, conduct complete documentation with standard formats related to handling problems and disseminate information and communicate the existing processes to all staff involved actively, so that the management of IT governance is there can be stable and controlled.